Leftover or Individualised? Representations of Chinese Single Womanhood in Western English-language News Media. Issue 2 (3rd April 2023) - Yu, Yating; Tian, Felicia F.
ABSTRACT: Since 2007, Chinese state-run media has used the term 'leftover women' to describe single women who are 27 or above. While considerable research has examined patriarchal discourse surrounding China's 'leftover women' in the Chinese state-run media, very little scholarship has explored the female individualisation discourse that emphasises independence and self-actualisation in Western English-language news outlets. To fill this gap, this study employed feminist critical discourse analysis to examine how the female individualisation discourse is constructed in a bid to advocate gender equality in 55 articles collected from the Western English-language news media. The analysis found three predominant themes underlying the female individualisation discourse: critiques of patriarchal social practices; pursuit of true love and self-actualisation; and advocacy of single women's reproductive rights. These themes are formulated by various discursive strategies – specifically, membership categorisation, scientific rationalisation, authorisation and metaphor. This study sheds light on the discursive construction of the female individualisation discourse that endeavours to empower single women in the Western English-language news media.